New Species and New Records of Apocephalus Coquillett (Diptera: Phoridae) that Parasitize Ants (Hymenoptera: Formicidae) in South America - Brown, B. V. (2010)
The following new species of Apocephalus ant-parasitizing flies are described: Apocephalus exlobicornis Brown & Disney, A. exstriatus Brown & Disney, A. flavitenuipes Brown & Disney, A. intermedius Brown & Disney, A. longisetarum Brown & Disney, A. necdivergens Brown & Disney, A. noetingerorum Brown & Disney, A. penicillatus Brown & Disney, and A. philhispidus Brown & Disney. Host records are reported for each species, as well as new host records for the previously described A. mucronatus Borgmeier, A. neivai Borgmeier, A. setitarsus Brown, A. velutinus Borgmeier, A. viscosae Disney, and for one further unnamed species.